Changes of gut microbiota structure in rats infected with Toxoplasma gondii - Lv, Qing-Bo; Ma, He; Wei, Jiaqi; Qin, Yi-Feng; Qiu, Hong-Yu; Ni, Hong-Bo; Yang, Li-Hua; Cao, Hongwei (Frontiers in Cellular and Infection Microbiology, 2022)
Toxoplasma gondii (T. gondii) infection can cause intestinal inflammation in rodents and significantly alters the structure of gut microbiota. However, the effects of different T. gondii genotypes on the gut microbiota of rats remain unclear. In this study, acute and chronic T. gondii infection in Fischer 344 rats was induced artificially by intraperitoneal injection of tachyzoites PYS (Chinese 1 ToxoDB#9) and PRU (Type II). Fecal 16S rRNA gene amplicon sequencing was employed to analyze the gut microbiota structure at different stages of infection, and to compare the effects of infection by two T. gondii genotypes. Our results suggested that the infection led to structural changes of gut microbiota in rats. At the acute infection stage, the microbiota diversity increased, while both diversity and abundance of beneficial bacteria decreased at the chronic infection stage. The differences of microbiota structure were caused by strains of different genotypes. However, the diversity changes were consistent. This study demonstrates that the gut microbiota plays an important role in T. gondii infection in rats. The data will improve our understanding of the association between T. gondii infection and gut microbiota in rodents.